Expression of miR-127, miR-154, and miR-183 in Medullary Thy-roid Carcinoma Tumors - Mahsa RAHMANI SAMANI; Marjan ZARIF-YEGANEH; Atefeh MEHRABI; Amir Nader EMAMI RAZAVI; Sara SHEIKHOLESLAMI; Mehdi HEDAYATI (Tehran University of Medical Sciences, 2021)
Background: Medullary thyroid cancer (MTC) accounts for 5%-10% of all thyroid cancers, but causes 13% of all thyroid cancer related deaths. MicroRNAs (miRs) have key functions in the development and progression of MTC. Altered expression of some miRs has been reported in many human cancers, including Thyroid cancer. Therefore, we aimed to analyze the expression of miR-154, miR-183 and miR-127 in MTC tumor tissues. Methods: In this case-control study, 15 MTC Formalin-fixed, paraffin-embedded (FFPE) tissue samples and 15 adjacent normal thyroid FFPE tissues, as a control group, were collected from Taleghani, and Loghman Hakim Hospitals, Tehran, Iran since 2005 till 2015. After RNA extraction and cDNA synthesis, the expression of miR-127, miR-154 and miR-183 was measured by quantitative Real-Time Polymerase Chain Reaction (qRT-PCR). Results: Our data showed a significant increase in the expression of miR-127 in MTC samples in comparison with the control group (P<0.05). Although miR-154 and miR-183 expression levels had increase expression in MTC tumors, this change was not statistically significant. Conclusion: The miR-127 could be considered as a prognostic, diagnostic and therapeutic marker for the management of MTC, and it is proposed for further investigation to fully establish the role of this miRNA in MTC.